Probing EEG activity in the targeted cortex after focal transcranial electrical stimulation - Syoichi Tashiro; Hartwig R. Siebner; Angeliki Charalampaki; Cihan Göksu; Guilherme B. Saturnino; Axel Thielscher; Leo Tomasevic (Brain Stimulation, 2020)
Background: Recording electroencephalography (EEG) from the targeted cortex immediately before and after focal transcranial electrical stimulation (TES) remains a challenge. Methods: We introduce a hybrid stimulation-recording approach where a single EEG electrode is inserted into the inner electrode of a double-ring montage for focal TES. The new combined electrode was placed at the C3 position of the EEG 10–20 system. Neuronal activity was recorded in two volunteers before and after 20 Hz alternating-current TES at peak-to-peak intensities of 1 and 2 mA. TES-induced electric field distributions were simulated with SIMNIBS software. Results: Using the hybrid stimulation-recording set-up, EEG activity was successfully recorded directly before and after TES. Simulations revealed comparable electrical fields in the stimulated cortex for the pseudomonopolar montage with and without embedded EEG electrode. Conclusion: The hybrid TES-EEG approach can be used to probe after-effects of focal TES on neuronal activity in the targeted cortex.